Empirical Problems of Savings Calculation in Electronic Reverse Auction - Delina,Radoslav (Universidad de Talca, 2019)
Abstract: The impact of reverse auction adoption has been a very important issue recently and is the subject of many studies. We are extending research results in the field of empirical studies by examining problems with reliability of methods for cost savings calculation of electronic reverse auction adoption in business processes. Reliability of savings proclamation in research studies or promotional materials is crucial for understanding real impact, benchmarking studies or comparison of several auction strategies from different auction environments. From our experience and empirical examinations, the problem for savings calculations is based on reliability and suitability of comparative or sometimes called expected price as the core factor for savings calculations when comparing with winning price. Our empirical study was based on real data from 1198 reverse auctions in Slovak commercial sector. On the base of our study, the most frequent strategy for electronic reverse auction adoption is multi-phase auction with first phase using sealed bid format. We have identified that reliability of using comparative prices as parameter for cost savings calculations vary according to different auction situations or settings and number of participants, auction volume and ratio of new participants are very sensitive for the reliability of savings calculations.